UPAYA MENINGKATKAN PRESTASI BELAJAR BAHASA INDONESIA MATERI KALIMAT MAJEMUK SETARA MELALUI MODEL BELAJAR KELOMPOK PADA KELAS V DI SEKOLAH DASAR NEGERI 1 SUKARAME - Sutini, Sutini (Lentera: Jurnal Ilmiah Kependidikan, 2016)
The objective of this research is to increase the learning achievement in Bahasa Indonesia subject using group learning model. This study is classroom action research. The participants come from the fifth grade students of SD Negeri 1 Sukarame Bandar Lampung. Based on research finding, it is found that group learning model can improve students’ learning achievement of Bahasa Indonesia. Usage Learning Group method make learning more meaningful for students, which is indicated by the increased value of the average grade of 55.00 before Cycle Cycle I then became 62.91 1 meeting and at the meeting of two increases averaged into 73.58. The average value of Cycle II meeting 1 for 77.08 and then at a meeting 2 increased the average value of students to be 83.75. Usage Learning Methods Group is very helpful in understanding the subject matter for most learners.